2014
DOI: 10.1097/brs.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Association of Postoperative Shoulder Balance With Adding-on in Lenke Type II Adolescent Idiopathic Scoliosis

Abstract: The postoperative shoulder balance and postoperative distal adding-on were weakly but significantly associated with each other, and both shoulder imbalance and adding-on need to be prevented in Lenke type 2 curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 18 publications
1
47
3
4
Order By: Relevance
“…This might have clinical significance, as scoliosis will affect the spine in both the coronal plane and the sagittal plane. This study also did not analyze the influence of the lumbar modifier on shoulder imbalance as a recent study by Cao et al [32] showed an association between distal adding on phenomenon with shoulder imbalance. There is still subjectivity in clinical grading of neck tilt despite strong inter and intraobserver agreement.…”
Section: Discussionmentioning
confidence: 95%
“…This might have clinical significance, as scoliosis will affect the spine in both the coronal plane and the sagittal plane. This study also did not analyze the influence of the lumbar modifier on shoulder imbalance as a recent study by Cao et al [32] showed an association between distal adding on phenomenon with shoulder imbalance. There is still subjectivity in clinical grading of neck tilt despite strong inter and intraobserver agreement.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on thoracic AIS have only evaluated Lenke 2 AIS as part of a larger thoracic AIS sample treated with posterior instrumentation. Therefore, few reports have investigated surgical outcomes for Lenke 2 AIS alone [2,3,13], and the optimal surgical strategy remains controversial. Shoulder balance restoration and maintenance and normal sagittal contour are important AIS treatment measures, in addition to satisfactory main thoracic (MT) and compensatory thoracolumbar and lumbar (TL/L) curve correction.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder imbalance may cause adding on. 6 Therefore, Lenke 2AR type scoliosis may be at highest risk of adding on and little literature has speci cally focus on this topic. Moreover, as far as we know, the clinical impact of adding on was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In Lenke 2 scoliosis, the mechanism of distal adding on is even more complicated because of the underlying compensation of shoulder imbalance and little literature has explored the association between shoulder imbalance and adding on. 6 Lenke 1A was divided into two different lumbar sub-types according to the tilt direction of L4. 7 Lenke 1AR was reported to have higher incidence of adding on.…”
Section: Introductionmentioning
confidence: 99%